2012
DOI: 10.1007/s11894-012-0287-z
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of SpyGlass™ Choledochoscopy in the Diagnosis and Treatment of Biliary Disorders

Abstract: Peroral choledochoscopy was first described in the 1970s, but the use of earlier generation choledochoscopes was significantly limited by complex equipment setup and fragility resulting in high repair costs. In late 2006, the SpyGlass Direct Visualization System (Boston Scientific Corp, Natick, MA, USA) was introduced to the market. It is a single-operator cholangioscopy platform and improves upon many shortcomings of the dual-operator systems. Currently, the two main indications for its use are evaluation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 47 publications
0
39
0
1
Order By: Relevance
“…However, intraductal endoscopy is generally believed to be a safe procedure with relatively few complications that are comparable to those reported for ERCP [45]. These potential complications associated with cholangioscopy are numerous and range from relatively mild life-threatening sequelae conditions, including the following: cholangitis (most common complication), bacteremia, abdominal pain, pancreatitis, hypotension, nausea, liver abscess, radiculopathy, bile duct drilling (from the guide-wire), amylase and lipase elevation without clinical pancreatitis, and systemic inflammatory syndrome [45]. In a retrospective study including 402 ERCPs with cholangioscopy (a minority with SpyGlass® system) of a total of 3475 ERCPs, there was a higher rate of adverse events in the combination group (7% vs. 2.9%) [46].…”
Section: Complications and Safety Profilementioning
confidence: 97%
See 1 more Smart Citation
“…However, intraductal endoscopy is generally believed to be a safe procedure with relatively few complications that are comparable to those reported for ERCP [45]. These potential complications associated with cholangioscopy are numerous and range from relatively mild life-threatening sequelae conditions, including the following: cholangitis (most common complication), bacteremia, abdominal pain, pancreatitis, hypotension, nausea, liver abscess, radiculopathy, bile duct drilling (from the guide-wire), amylase and lipase elevation without clinical pancreatitis, and systemic inflammatory syndrome [45]. In a retrospective study including 402 ERCPs with cholangioscopy (a minority with SpyGlass® system) of a total of 3475 ERCPs, there was a higher rate of adverse events in the combination group (7% vs. 2.9%) [46].…”
Section: Complications and Safety Profilementioning
confidence: 97%
“…Intraductal endoscopy can assist in removing these difficult stones, by allowing direct visualization and guiding lithotripsy. Furthermore, standard fluoroscopy based cholangiograms routinely loosen remaining stones or stone fragments after lithotripsy [24]. Parsi et al [25] were able to diagnose at least 29% of ERCP-lost gallstones by later cholangioscopy, leading them to conclude that the lost stones rates in ERCP may be higher than previously thought.…”
Section: Therapeutic Applicationsmentioning
confidence: 99%
“…It has been shown that direct visualization with the cholangioscopy system improves the accuracy of cholangiographic findings in evaluating patients with biliary obstructive symptoms of indeterminate origin [3, 4, 1215]. Cholangioscopy also allows for obtaining biopsies under direct visualization.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, new methods, such as endoscopic ultrasound-guided FNA or spyglass cholangioscopy, have been introduced for evaluating biliary strictures 1921. However, we consider that tissue sampling, particularly TTS, would continue to be an essential procedure with its easy feasibility and safety.…”
Section: Discussionmentioning
confidence: 99%